PENGARUH LINGKUNGAN, MOTIVASI SERTA DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR CAMAT HAMPARAN PERAK DELI SERDANG - Sinto Sinto; Syamsul Bahri Surbakti; Akman Daulay; Nur'ainun Nur'ainun; Afrilia Afna (Jurnal Ecoment Global, 2023)
The purpose of this study is to determine the extent to which the influence of the environment, motivation, and work discipline of employees in the Hamparan Perak sub-district office, Deliserdang, where the process is carried out using quantitative descriptive-analytical methods in which supporting literature uses journals that are by the theme of the discussion. For data analysis, using the multiple linear regression approach by testing data validation and mapping with the normality test, the results of this study are that the environment, motivation, and work discipline do not significantly influence employee performance by 34.3%, while the remaining is 65. 7% is an independent variable that is excluded from this research study